PENERAPAN PENDEKATAN PENGAJARAN DAN PENGETAHUAN AWAL SISWA TERHADAP KEMAMPUAN BERKOMUNIKASI DALAM PEMAHAMAN MATERI PELAJARAN EKONOMI BAGI SISWA KELAS VII - ADI SUPRAYITNO (EQUILIBRIUM : Jurnal Ilmiah Ekonomi dan Pembelajarannya, 2013)
In the Actifity The purpose of this study is to describe the effect of th implementation of  based on REE instruction and regular Economical instruction and prior knowledge on Economical communication capabilities and understanding of grade 7 Sunior High School (SMP) students.  The study was carried out through a preliminary survey continuedby an experiment using factorial design with non-equivalent control group of Junior High Schools at Madiun cities.  The samples were choosen by cluster random sampling technique. The data were analyzed by using multivariat nalysis of covariance (MANCOVA) factorial 2 x 2.  This study showed that, for achievement of Economical communication capabilities and understanding, Economical instruction with REE was better than regular Economical instruction, the prior knowledge had a positive effec, and they was no interaction effect between Economical intruction (based on REE and regular) and prior knowledge (high and low).